Marketing Mix Strategi Pada Supermarket Sakinah Berdasarkan Maqashid Syariah - Icksan Nurchoiri; Masyhudan Dardiri; Tri Sudarwanto (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study describes the Implementation of Marketing Mix in the Islamic Maqashid Perspective in Sakinah Supermarket Surabaya. This study aims to find out how Sakinah Supermarket's efforts implement Marketing Mix from the perspective of Maqashid Syariah. The implementation of the Marketing Mix strategy carried out by Sakinah Supermarket by reviewing using the Maqashid Syariah business ethics principles, this theory is by the trading principles carried out by Rasulullah SAW. The Marketing Mix strategy used for this research is the 4P Marketing Mix including product, price, place, and promotion. This research method uses qualitative methods with data collection techniques of interviews, observation, and documentation. The validity of the data uses trust, transferability, dependability, and” certainty.The results of this study are the Implementation of a Marketing Mix from the perspective of Maqashid Syariah ethics which has been implemented in the sakinah supermarkets in Surabaya for sakinah supermarket products that only sell proper and halal products that are MUI certified and have excellent product quality, for the prices of sakinah supermarkets take high profits. very reasonable from 5% -10%, and has a very strategic place for the community, Sakinah Supermarket in conducting promotions based on honesty and the products included in the discount have good quality and packaging. The conclusion from this study is that Sakinah supermarkets implement a marketing mix with Hifdz ad-din's maqasid syariah